Cyclin D1 overexpression supports stable EBV infection in nasopharyngeal epithelial cells - Tsang, Chi Man (National Academy of Sciences, 2012)
Undifferentiated nasopharyngeal carcinomas (NPCs) are commonly present with latent EBV infection. However, events regulating EBV infection at early stages of the disease and the role of EBV in disease pathogenesis are largely undefined. Genetic alterations leading to activation of cyclin D1 signaling in premalignant nasopharyngeal epithelial (NPE) cells have been postulated to predispose cells to EBV infection. We previously reported that loss of p16, a negative regulator of cyclin D1 signaling, is a frequent feature of NPC tumors. Here, we report that early premalignant lesions of nasopharyngeal epithelium overexpress cyclin D1. Furthermore, overexpression of cyclin D1 is closely associated with EBV infection. Therefore we investigated the potential role of cyclin D1 overexpression in dysplastic NPE cells in vitro. In human telomerase reverse transcriptase-immortalized NPE cells, overexpression of cyclin D1 or a p16-resistant form of CDK4 (CDK4(R24C)) suppressed differentiation. This suppression may have implications for the close association of EBV infection with undifferentiated NPC. In these in vitro models, we found that cellular growth arrest and senescence occurred in EBV-infected cell populations immediately after infection. Nevertheless, overexpression of cyclin D1 or a p16-resistant form of CDK4 or knockdown of p16 in the human telomerase reverse transcriptase-immortalized NPE cell lines could counteract the EBV-induced growth arrest and senescence. We conclude that dysregulated expression of cyclin D1 in NPE cells may contribute to NPC pathogenesis by enabling persistent infection of EBV.